Perjuangan Politik Datuk Badiuzzaman Surbakti Dalam Perang Sunggal - Farid Mas Hadi (Dinamika Politik, 2012)
This study is the study of the political struggle in the Sunggal War ancestor Datuk Badiuzzaman Surbakti. Discuss the focus on what the strategy of political struggle Datuk Badiuzzaman Surbakti In Sunggal War (1872-1895). The findings of this study include some strategies used political struggle. First, diplomacy with some of the tribes, the Karo tribe, Aceh Gayo tribe, ethnic Malays; Second, a guerrilla war; Third, using a strategy of scorched earth. The method used is descriptive-qualitative method that is intended to describe an event in more detail.Keywords: Conflict, power, war.